Modification of an N-Methyl Group toward a New Energetic Melt-Castable Material with a Good Energy-Stability Balance - Chen, Fang; Song, Siwei; Zhang, Qinghua; Wang, Yi (Synlett, 2024)
The energy and stability properties of energetic materials are often contradictory to each other (e.g., high energy vs low thermal stability). There is no doubt that it is still challenging to explore the effective balance between energetic performance and molecular stability, especially for melt-castable materials. In this study, we selected the 4-methoxy-3,5-dinitropyrazole framework and a stable nitro group to design a new energetic melt-castable compound, namely 4-methoxy-3,5-dinitro-1-(nitromethyl)-1H-pyrazole (MDNNMP). Compared with the N-methylation product DMDNP and the nitrato-substituted derivative MC-7, MDNNMP exhibits a better balanced performance, including good thermal stability (Td: 203.7 °C), detonation velocity (Dv: 8099 m s–1) and impact sensitivity (20 J). The favorable balanced performance of MDNNMP suggests that it is a suitable candidate as a high-performance melt-castable material. Additionally, compared with the nitratomethyl group, the nitromethyl group demonstrates superior advantages in performance regulation.
Keywords: energetic material; melt-castable material; balanced properties; energy; stability